2023
DOI: 10.1186/s12879-023-08720-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID 19 infection clinical features in pediatric patients in Southwestern Iran: a cross-sectional, multi-center study

Marzieh Jamalidoust,
Mohsen Jalil,
Zahra Ashkan
et al.

Abstract: With the SARS-CoV-2 pandemic, the impact of recent coronavirus, especially in children, cannot be ignored. In this study, we evaluated the SARS-CoV-2 infection rates and associated features in children less than 18 years of age in “Fars” and “Kohgiluyeh and Boyer Ahmad”, provinces, Iran. 5943 children who were suspected cases to SARS-CoV-2 infection were enrolled in this study. Demographic and clinical data of SARS-CoV-2 patients were collected from 16 February 2020 to 20 June 2021. Underlying conditions were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Another study in the Golestan province of northern Iran included 91 confirmed cases aged between 0 and 18 years. Of these, 17.5% (16) required ICU hospitalization, and 8.8% (91) resulted in mortality events [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in the Golestan province of northern Iran included 91 confirmed cases aged between 0 and 18 years. Of these, 17.5% (16) required ICU hospitalization, and 8.8% (91) resulted in mortality events [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%